Occurrence of powdery mildew disease of Gerbera in Kerala - N M Praveen; Reshmy Vijayaraghavan; S Beena; S Krishnan (Journal of Horticultural Sciences, 2018)
A purposive sampling survey on the hilly tracts of Wayanad, Kerala revealed the existence of powdery mildew disease in gerbera crops, grown under both protected and open field condition. Among the other fungal diseases of gerbera, powdery mildew disease causes decisive damage to the ornamental cut flower crop, thereby decline in the industrial value of the crop. Symptom of the disease include as white powdery mat on the upper surface of leaf lamina that gradually turned pale yellow to brown. Powdery mildew existed in two locations of Wayanad viz., Ambalavayal and Chulliyode where highest per cent disease severity (PDS) of 50.72 was observed at Chulliyode and 47.2 per cent was observed at Ambalavayal during November-December. In Ambalavayal, the disease was non-significant and no correlation existed between weather parameters and disease progress. But, in Chulliyode, correlation studies revealed that it was significant with positive correlation to relative humidity and a reverse relation existed with temperature and rainfall. The weather data clearly depicts that at a low rainfall of 96 mm and above average relative humidity of 80.27 per cent during November-December was the congenial factor influencing the disease development. But during summer, decline in relative humidity (78.37%) and rainfall (63.13 mm) caused a slight reduction in mean per cent disease severity of 49.12 per cent and 33.6 per cent at Chulliyode and Ambalavayal respectively. Morohological and cultural characters of the pathogen depicts presence of two distinct organism viz., Golovinomyces cichoracearum (Erysiphe cichoracearum) and Podosphaera sp. as the causative organism of the disease. Golovinomyces cichoracearumproduced hyaline, septate mycelia with globose conidia with irregular peripheral end formed in a chain and Podosphaera sp. produced superficial, hyaline, coenocytic mycelium with oval or ellipsoidal, catenate conidia with dimension ranging from 22.1-30.18 x 13.36-18.08ìm formed in unbranched erect conidiophores.